Validade da Lei de Okun em três regiões metropolitanas do Brasil (2002-2014) - Gois, Rodrigo Melo (2017)
The Okun’s Law has been frequently addressed in macroeconomic studies around the world, mostly in national levels, with few studies that estimate the relationship at regional level. This work, using 2002q1-2014q3 quarterly data, estimated the Okun coefficients for Brazil and for the metropolitan areas of Belo Horizonte, Porto Alegre and Sao Paulo. The conclusion is that Okun’s Law is valid in Brazil and in one of the three metropolitan regions studied, and there are regional differences in the responsiveness of labor markets to output fluctuations and deviations from their long-term levels, which, according to the literature, implies the need to implement unemployment policies that not only meet the regional disparities in the labor market, but also the elasticity of the labor market to changes in economic activity in each location.